Characteristic Test of Diode Based Multisim Software - Djalal, Muhammad Ruswandi; Rahmat, Rahmat (PROtek : Jurnal Ilmiah Teknik Elektro, 2020)
In this study, a diode characteristic testing will be conducted, namely the characteristics of forward bias and reverse bias using Multisim software. Diode components are mostly applied to electronic circuits, so a simulation is needed to determine the performance of the diode before it is applied to the circuit. The test to be carried out this time includes making a forward bias circuit and back bias on a diode, describing the characteristics of the diode, determining the diode's working point for a particular condition, and determining dc diode resistance in the forward bias and reverse bias. From the results of testing the forward bias characteristic, it can be seen that the silicon diode IN 4001 in forward bias increases the small current until the diode voltage (Vd) reaches its knee voltage (Vk) around 0.6 V - 0.7 V. After going through knee stress (Vk), then the increase in large currents. The workings of diodes like this can be said as diodes with deviant or biased currents. Whereas the reverse bias current is almost constant (almost close to zero) even though the voltage is increased continuously until it reaches a voltage of 50 V. How it works like this is called a diode with reverse current.